SOCA 2320 and ENGL 1330 students support PPR Sg. Bonus families - Syed Hussien, Sh Fatimah Alzahrah; Ramlan, Wan Nur Madiha (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), IIUM, 2024)
Throughout Semester II, 2023/2024, 118 students from the Department of Sociology and Anthropology and Department of English Language and Literature, had jointly conducted various projects for SOCA 2320: Sociology of Marriage and Family and ENGL 1330: Reading Poetry, under the Synergised Academic Activity (SAA) initiative by AbuHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences (AHAS KIRKHS). The SAA approach is introduced by AHAS KIRKHS to encourage students and academics to establish various community partnerships and networks through projects and activities which reflect knowledge and learning in their classes.